O-Fucosyltransferase SPINDLY attenuates auxin-induced fruit growth by inhibiting ARF6/8-coactivator mediator complex interaction in Arabidopsis - Yan Wang; Seamus Kelley; Rodolfo Zentella; Jianhong Hu; Hua Wei; Lei Wang; Jeffrey Shabanowitz; Donald F. Hunt; Tai-ping Sun (Nature Communications)
Abstract The phytohormone auxin plays a pivotal role in promoting fruit initiation and growth upon fertilization in flowering plants. Upregulation of auxin signaling by genetic mutations or exogenous auxin treatment can induce seedless fruit formation from unpollinated ovaries, termed parthenocarpy. Recent studies suggested that the class A AUXIN RESPONSE FACTOR6 (ARF6) and ARF8 in Arabidopsis play dual functions by first inhibiting fruit initiation when complexed with unidentified corepressor IAA protein(s) before pollination, and later promoting fruit growth after fertilization as ARF dimers. However, whether and how posttranslational modification(s) regulate ARF6- and ARF8-mediated fruit growth were unknown. In this study, we reveal that both ARF6 and ARF8 are O-fucosylated in their middle region (MR) by SPINDLY (SPY), a unique nucleocytoplasmic protein O-fucosyltransferase, which catalyzes the addition of a fucose moiety to specific Ser/Thr residues of target proteins. Epistasis, biochemical and transcriptome analyses indicate that ARF6 and ARF8 are downstream of SPY, but ARF8 plays a more predominant role in parthenocarpic fruit growth. Intriguingly, two ARF6/8-interacting proteins, the co-repressor IAA9 and MED8, a subunit of the coactivator Mediator complex, are also O-fucosylated by SPY. Biochemical assays demonstrate that SPY-mediated O-fucosylation of these proteins reduces ARF-MED8 interaction, which leads to enhanced transcription repression activity of the ARF6/8-IAA9 complex but impaired transactivation activities of ARF6/8. Our study unveils the role of protein O-fucosylation by SPY in attenuating auxin-triggered fruit growth through modulation of activities of key transcription factors, a co-repressor and the coactivator MED complex.